Assessment on Genetic Diversity and Relationship of 19 Bird Pepper Genotypes Based on Morphological and SSR Markers - Rustikawati, Rustikawati; Herison, Catur; Sutrawati, Mimi; Prameswari, Wuri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
A comprehensive assessment of genetic diversity offers invaluable insights to breeders. This study aims to analyze the genetic diversity of 19 cayenne pepper genotypes using morphological and SSR markers. Morphological markers are essential for evaluating visible traits while SSR markers provide deeper insights into genetic variation. Using both morphological and SSR markers provides a more robust, multidimensional approach to understanding genetic diversity. Morphological characterization was conducted on 19 bird pepper genotypes using 30 distinct traits, further divided into 95 sub-traits, to evaluate vegetative and generative growths. Molecular profiling was carried out using 10 SSR primers. The SSR analysis yielded 80 scorable bands, of which 72 were polymorphic. The high polymorphic information content suggests that these markers were effective in differentiating the genotypes. The genetic diversity within the population was substantially high, providing valuable genetic material for breeding programs. Genetic similarity analysis divided the population into six distinct groups. Among them, Group I (genotype A05 Taiwan) and Group VI (genotype A02, Bengkulu Indonesia) formed unique, solitary groups, distinguishing them from other clusters. This information is highly beneficial for bird pepper cultivar development, emphasizing the importance of incorporating additional traits to align with the cultivar development of high yielding and saline-stress tolerance.